Kompetensi Sumber Daya Manusia, Sistem Pengendalian Internal dan Pemanfaatan Teknologi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Mega Suryani Hutabri (Postgraduate Program Merdeka University, 2023)
This study aims to analyse the effect of human resource competence, internal control and information technology utilization on the quality of local government financial reports. This research is quantitative research using secondary data and the type of research used is explanatory. The sample of this research is the finance department or the finance department in the Regional Apparatus Organisation of Malang City. The number of samples in this study were 34 re-spondents. The analysis technique used is multiple linear regression. Based on the results of the analysis, it shows that human resource competence and the inter-nal control system affect the quality of regional financial reports, while the use of information technology has no effect on the quality of regional financial reports.DOI: https://doi.org/10.26905/afr.v6i3.8401